Pengukuran Panjang Simulasi Retak Permukaan dengan Teknik Perambatan Gelombang Ultrasonik Permukaan - Ashadi Salim (Bina Nusantara University, 2011)
The length measurement of the surface crack simulation using surface ultrasonic wave method is performed for surface crack length of 5, 10, 15, 17.5, 20 and 22.5 mm. Each crack has the orientation of 22.50, 450, 67.50, and 900 against the surface of the sample. The method is similar to the transmission technique, where the transmitting and receiving probes are arranged face-to-face against the crack mouth. The surface wave pulse is high enough to be distinguished from the pulse of the coming waves as the result of mode conversion that occurs from the crack tip. The deviation of the measurement of the length was 8% in the average.